A diferença vai à escola: problematizando as articulações discursivas e epistemológicas sobre os marcadores sociais da diferença no espaço educacional - Sales, Romualdo da Silva (2019)
The reflections presented in this text presents with the processes operationalized control and domination within the school, problematizing the relations of power established by them, having as point of reference the operative discourses on social markers of difference: race, gender and sexuality. In this way, I develop a study that problematizes the epistemological bases that underpin these systems of domination contributing to the construction of social identification processes, investing in the production of differences as relational complexes. In this perspective, the purpose of this work is realize and understand, from the Estanislau Eloy Municipal School, the impacts of the transformations under way in Brazil, mapping the discursive and epistemological interlocutions articulated to the processes of control and domination, that happens in education field. In this way, the problematizations presented here, shows that the school and curriculum are important devices that make dynamics of control and social domination, with reference to the production of subjects normalized and abject. These dynamics contribute to the consolidation of social values previously established at the same time as they invest against subjects that blur the boundaries set by discourses on gender identities and sexualities considered deviant, slipping into forms of physical violence and within and outside educational space.